USING PARAGRAPH ANALYSIS IN TEACHING GRAMMAR - Yuli Herman (ELP (Journal of English Language Pedagogy), 2022)
This experimental study assessed the effectiveness of using paragraph analysis in teaching grammar, especially in improving students’ knowledge and comprehension. In implementing this strategy students were asked to analyze every sentences in a paragraph where in every paragraph has misused of tenses and verb. During the process, the class activity mostly was in form of discussion. First activity was reading the text. Then, the students were asked to identify the tense of every sentences in the paragraph and analyzed whether or not there was a mistake in every sentences. The next step was students discuss in a group and reconstructed the inappropriate sentences. Before giving treatment to the students, they were given initial test. Then, at the end of the research the students were given final test. Both of the result of the tests were calculated by using t-test. Level of significant applied is 95% or 0.005. The calculation result was 0.004 which means there was a significant difference before implementing paragraph analysis and after the treatment.